Luc Brisson e Jean-François Pradeau (Sous La Direction de). Plotin Traités 45-50. Paris: Éditions Flammarion, 2009, pp. 515. - Baracat Júnior, José (Revista Archai, 2010)
Resenha Luc Brisson e Jean-François Pradeau (Sous La Direction de). Plotin Traités 45-50. Paris: Éditions Flammarion, 2009, pp. 515.